1984
DOI: 10.1083/jcb.99.6.2056
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-collagen adhesion: inhibition by a monoclonal antibody that binds glycoprotein IIb.

Abstract: TO identify platelet surface structures involved in adhesion to collagen, the effect of 16 murine antiplatelet membrane hybridoma antibodies were tested in a defined, in vitro assay. Four of these antibodies inhibited platelet-collagen adhesion and reacted with a polypeptide with Mr ~ 125,000, as determined by immunoblots after gel electrophoresis under reducing conditions. Through detailed studies with one of these antibodies, the monoclonal antibody PMI-1, the relevant antigen was identified as platelet glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(58 citation statements)
references
References 24 publications
2
56
0
Order By: Relevance
“…The mouse monoclonal antibody (PMi-l) was prepared and thoroughly characterized elsewhere by Shadle et al (38) and was kindly provided by Dr. Mark H. Ginsberg (Scripps Clinic and Research Foundation, La Jolla, CA). In brief, this monoclonal antibody was derived from mice immunized with platelet plasma membranes and was selected on the basis of its ability to inhibit platelet adhesion to collagen.…”
Section: Monoclonal Antibody (Pmi-1) Against Gpllbamentioning
confidence: 99%
“…The mouse monoclonal antibody (PMi-l) was prepared and thoroughly characterized elsewhere by Shadle et al (38) and was kindly provided by Dr. Mark H. Ginsberg (Scripps Clinic and Research Foundation, La Jolla, CA). In brief, this monoclonal antibody was derived from mice immunized with platelet plasma membranes and was selected on the basis of its ability to inhibit platelet adhesion to collagen.…”
Section: Monoclonal Antibody (Pmi-1) Against Gpllbamentioning
confidence: 99%
“…Several platelet membrane proteins have been reported as the receptor for the collagen which is a major component in the vessel wall (Shadle et al 1984;Nieuwenhuis et al 1986 ;Chiang et al 1987 ;Sugiyama et al 1987). Platelet FXIII was recently described as collagen receptor for bovine platelet-collagen aggregation interaction (Saito et al 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is one of the important components among the vascular subendothelium and several reports on the platelet membrane receptors which are involved in platelet-collagen interaction have been described in recent years (Shadle et al 1984; Tsunehisa et al 1984;Chiang et al 1987; Kotite and Cunningham 1986;Nieuwenhuis et al 1986 ; Sugiyama et al 1987). Saito et al (1986) have reported that bovine factor XIII (FXIII) may be a platelet receptor for collagen.…”
mentioning
confidence: 99%
“…Our strategy allowed recognition of epitopes not exposed or inaccessible on the resting integrin. In contrast, all other anti-LIBS or activation-dependent mAbs were produced using either whole platelets (27), platelet membranes (26,28), purified ␣ IIb ␤ 3 (5), purified ␣ IIb ␤ 3 mixed with RGDS (4), or synthetic ␣ IIb ␤ 3 peptides (29) as the immunogen. In addition, a single-chain variable fragment specific for activated ␣ IIb ␤ 3 was obtained using phage display against activated platelets (30).…”
Section: Discussionmentioning
confidence: 99%
“…Three types of anti-LIBS antibodies against ␣ IIb or ␤ 3 are described in the literature (a) with no effect on platelet aggregation (PMI-1, ␣ IIb -specific) (25,26), (b) with inhibition of platelet aggregation (anti-LIBS-1, ␤ 3 -specific) (4), and (c) with activation of ␣ IIb ␤ 3 (D3GP3, anti-LIBS-2, -3, -6, ␤ 3 -specific) (4,5,22). To our knowledge, 3C7 is the first anti-LIBS mAb against the complex of ␣ IIb ␤ 3 .…”
Section: Discussionmentioning
confidence: 99%